Assessment Reform in Science Fairness and Fear - Yung, Benny B.H.W (Contemporary Trends and Issues in Science Education, 2006)
The conclusions and recommendations made in the book are derived from a study of ten teachers in Hong Kong as they tried to change their practice following a reform of the Hong Kong assessment system. Hong Kong is simply a context that provided the opportunity to gather very rich and informative data on issues pertaining to assessment reforms which also have very wide implications in many countries' contexts. The book is written for practising teachers, teachers-in-training, teacher educators, policy makers and researchers who are interested in teachers' classroom practices, teacher beliefs, teacher professionalism, implementation of educational reforms in general and high stakes assessment reforms in particular. The structure of the book is organized in a manner that rapidly presents the case stories of the teachers to the readers. These stories can be helpful to all teachers, whether in training or experienced, in a number of ways: (1) as a set of ideas to be debated upon and to act as a springboard for reflection on the purposes of assessment in education and on the role of teachers in these purposes; (2) as examples of practice that can be compared to the readers' own existing practices; and (3) as a source of models of practice to apply and test in readers' own classrooms. These case stories are followed by a discussion of a number of issues that arise from this group of teachers' beliefs and practices. To cater for research-oriented readers, the relevant literature, theoretical underpinnings, and the intriguing research methodology that led to the case stories will appear as appendices.